Analysis of Differences in Riil Rates With INA-CBGs Rates of Inpatients Confirmed with Covid-19 at RSUD dr. Soehadi Prijonegoro Sragen - ira basuki; Sri Sugiarsi; Trismianto Asmo Sutrisno (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
The acceleration of handling Covid-19 is carried out in the form of providing health services to patients in hospitals that provide Covid-19 services. Financing of patients treated with certain emerging infectious diseases can be claimed to the Ministry of Health through the Director General of Health Services. There is a negative difference in the cost of patient care. The purpose of this study is to determine the difference between real rates and INA-CBGs rates in confirmed Covid-19 inpatients at dr. Soehadi Prijonegoro Sragen Hospital in semester 1 of 2022.This type of research is analytical observation with a comparative approach. The population of 275 medical record files used saturated samples. How to collect data by observation using checklists and documentation. The data analysis of this study is a univariate and bivariate analysis, the results of this study are the average real tariff of inpatient women Rp. 18,485,206.40, while the average tariff INA–CBGs is 18,101,971.27. Based on the Wilcoxon test, it can be concluded that there is no difference between the real tariff and the INA–CBGs tariff for inpatients confirmed with Covid-19 at dr. Soehadi Prijonegoro Sragen Hospital.